Strategi Fundraising dalam Memperoleh Pendapatan Dana pada Organisasi Relawan Gesit Bone - Az zulfa, Yuandini; Qudratullah (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2025)
This research aims to analyze the fundraising strategies implemented by Gesit Bone Volunteer Organization to generate revenue. The method used is qualitative with a descriptive approach, which is done through interviews and analyzing the organization's official documentation to detail the fundraising strategy implemented. The research results show that Gesit Bone Volunteer Organization implements two fundraising strategy patterns, one of which uses the crowdfunding platform “KitaBisa” as the main source of funding. The process of fundraising is done by preparing a structured assessment and draft budget (RAB) to increase transparency and trust among donors. This approach is not only effective in fundraising but also minimizes the negative risks that are often encountered in traditional street fundraising. Meanwhile, the second strategy is the use of image campaigns through social media. Gesit Bone Volunteer Organization regularly shares documentation of activities such as photos, short videos and other creative content to attract attention and arouse public emotions. This strategy is to enhance the organization's image as a professional and trustworthy social institution and expand the donor network. This research also uses relevant fundraising theories to analyze the approach of Gesit Bone Volunteer Organization, such as the use of digital technology, transparency in fund management and communication creativity, which are key factors in the success of Gesit Bone Volunteer Organization's fundraising strategy in the modern era.